THE EFFECT OF PREGNANT KNOWLEDGE AND HUSBAND SUPPORT ON THE IDEAL K1 VISIT AT POLINDES SIDODADI, TAMAN DISTRICT SIDOARJO DISTRICT - THERESIA PRATIWI SUYANTI; Dwi Wahyu Wulan; Titi Maharani (Gema Bidan Indonesia, 2022)
The achievement of ANC K1 visits at the Sidodadi Polindes, Taman Sub-district, Sidoarjo Regency decreased as stated based on the PWS KIA Puskesmas Trosobo coverage of pregnant women The first visit (K1) in 2021 decreased compared to the previous coverage of pregnant women The first visit (K1) in 2020. Objective: This study aims to determine the effect of husband's knowledge and support on ideal K1 visits at the Sidodadi Polindes, Taman District, Sidoarjo Regency. This research design is an observational quantitative analytic study with a cross sectional research design. The sample of this research is pregnant women who visit K1 Ideal a total of 31 people with purposive sampling technique. The independent variable in this study was husband's knowledge and support, and the dependent variable in this study was the ideal K1 visit. The analysis used was Bivariate Analysis (Chi Square) with a 95% confidence level or 0.05. Most (66.7%) pregnant women with less knowledge did not do the Ideal K1 while all (100%) knowledgeable pregnant women did the Ideal K1. The results of the statistical test P Value 0.037 (α <0.05) which means that there is a significant influence between knowledge of pregnant women and ideal K1. Most (61.9%) pregnant women who do not get husband support do not do ideal K1, meanwhile half (50%) Pregnant women with the support of their husbands do K1 Ideal. Statistical test results P Value 0.013 (α<0.05) which means that there is a significant effect between Husband's Support and Ideal K1.